High-dose cytarabine consolidation with or without additional amsacrine and mitoxantrone in acute myeloid leukemia: results of the prospective randomized AML2003 trial - Schaich, Markus; Parmentier, Stefani; Kramer, Michael; Illmer, Thomas; Stölzel, Friedrich; Röllig, Christoph; Thiede, Christian; Hänel, Mathias; Schäfer-Eckart, Kerstin; Aulitzky, Walter; Einsele, Hermann; Ho, Anthony Dick; et al. (Journal of clinical oncology, 2013)
Purpose - To assess the treatment outcome benefit of multiagent consolidation in young adults with acute myeloid leukemia (AML) in a prospective, randomized, multicenter trial. - Patients and Methods - Between December 2003 and November 2009, 1,179 patients (median age, 48 years; range, 16 to 60 years) with untreated AML were randomly assigned at diagnosis to receive either standard high-dose cytarabine consolidation with three cycles of 18 g/m2 (3× HD-AraC) or multiagent consolidation with two cycles of mitoxantrone (30 mg/m2) plus cytarabine (12 g/m2) and one cycle of amsacrine (500 mg/m2) plus cytarabine (10 g/m2; MAC/MAMAC/MAC). Allogeneic and autologous hematopoietic stem-cell transplantations were performed in a risk-adapted and priority-based manner. Results - After double induction therapy using a 3 + 7 regimen including standard-dose cytarabine and daunorubicin, complete remission was achieved in 65% of patients. In the primary efficacy population of patients evaluable for consolidation outcomes, consolidation with either 3× HD-AraC or MAC/MAMC/MAC did not result in any significant difference in 3-year overall (69% v 64%; P = .18) or disease-free survival (46% v 48%; P = .99) according to the intention-to-treat analysis. Furthermore, MAC/MAMAC/MAC led to additional GI and hepatic toxicity and a higher rate of infection and bleeding, resulting in significantly shorter 3-year overall survival in the per-protocol analysis compared with 3× HD-AraC (63% v 72%; P = .04). - Conclusion - In younger adults with AML, multiagent consolidation using mitoxantrone and amsacrine in combination with high-dose cytarabine does not improve treatment outcome and confers additional toxicity.